Diazepam filled hard capsules intended for detoxification of patients addicted to benzodiazepines and Z-drugs - Franc, Aleš; Kubová, Kateřina; Elbl, Jan; Muselík, Jan; Vetchý, David; Šaloun, Jan; Opatřilová, Radka (European journal of hospital pharmacy, 2019)
OBJECTIVES: The abuse of benzodiazepines and Z-drugs reduces the quality of life of millions of addicted people worldwide. They cannot be discontinued abruptly due to harmful withdrawal symptoms. Detoxification is usually based on replacement of short/middle acting benzodiazepines or Z-drugs by diazepam and tapering the dose over time. In order to enhance patient adherence to an individual withdrawal plan, suitable diazepam dosage forms have to be available. Hard capsules containing an exact and uniform dose could be used for the relief of symptoms caused by altering the plasma level and overcoming psychogenic stress from the dose reduction. METHODS: This work demonstrates that capsules with a content of diazepam ranging from 2.125mg to 0.492 mg (dose decreasing always by 15%) cannot be easily prepared by standard mortar technology in a pharmacy. To meet mass and content uniformity European Pharmacopoeia criteria, capsules were prepared by improved technology based on the preparation of binary blends of calcium phosphate anhydrous and diazepam in descending concentrations in a high-speed mixer (time 30 s) and densification of about 10% during filling of the capsules. RESULTS: All batches (n=20) prepared by improved technology met the requirement for content uniformity compared with only nine batches prepared by standard mortar blender technology. Based on the process capability index, none of the samples prepared by standard technology fitted pharmacopeia limits at the statistically acceptable level. On the other hand, all batches prepared by improved technology exhibited acceptable process capability index. CONCLUSIONS: We have shown that at least 99.73% of batches prepared by our improved technology would meet the pharmacopoeia limits for content uniformity and are suitable for treatment of this type of addiction.
Keywords: Dose Tapering; Content Uniformity; Detoxification; Benzodiazepines; Withdrawal; Weight Uniformity; Capsules